Implementation of Basketball Extracurricular in Developing Student Discipline and Cooperation at Jabal Rahmah Mulia Boarding High School: Penelitian - T Maulana Abdullah Selian; Makhrianda Hadi Fitra; Wahyu Arkan Arisyandi; Alhamdi Cahyo Mourinof; Rifky Aulia Fahmi; Fathurrahman Raqi Lubis (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Education emphasizes not only academic ability but also character building such as discipline and teamwork. Extracurricular team sports activities, particularly basketball, play a strategic role in instilling these values. This study aims to describe the implementation of basketball extracurricular activities and their role in developing student discipline and teamwork at Jabal Rahmah Mulia Boarding High School. The study used a descriptive qualitative approach with 20 subjects consisting of students and coaches. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing, with validity through triangulation. The results showed that basketball activities were carried out in a structured and routine manner with the support of the school, coaches, and adequate facilities. The value of discipline is seen in student compliance with schedules, rules, equipment, and coach directions, while cooperation is reflected through interaction, team communication, role division, and mutual support. Participation in the 2025 AZA 3X3 Competition North Sumatra proves that the values ​​of discipline and teamwork built in training can be applied in competitive situations, thus basketball extracurricular activities play an important role in character education at boarding schools.